A decentralised P2P revision management system using a proactive mechanism. (3rd April 2006) - Takata, Katsuhiro; Ma, Jianhua
This paper presents a prototype and evaluations of the GRAM, a peer to peer (P2P) and a revision management system based on a proactive mechanism. GRAM performs revision collision prevention management and software source code synchronisation in a potential overlay network of peers connected via the internet or a LAN/WAN. This system provides four special features in comparison with other version management systems: higher system reliability and robustness, effective revision collision prevention using proactive agents, context aware environment for team software revision, and a unified XML format for configurations and history files as well as for system and agent exchange their control messages. Each peer of the GRAM system has a unique identifier provided by the JXTA framework, and holds two spaces: a shared space synchronised other peers' ones, and a workspace for a user's ordinary editing. Experimental results obtained with a prototype implementation on an enumerated network confirm GRAM's efficiency. By using GRAM, version managements of various software development projects can be comfortably conducted.